Forensic Examination as an Object of Administrative and Legal Regulation of International Cooperation (Law and Safety, 2020)
Forensic examination as an object of administrative and legal regulation of international cooperation has been studied. The author has analyzed and determined basic categories of the article: “examination”, “forensic examination”, “administrative and legal regulation”, “international cooperation”. The legal regulation of forensic examinations and forensic activities in Ukraine has been determined.It has been proved that forensic examination as an object of administrative and legal regulation of international cooperation is an organizational and legal activity of specialized entities (state specialized institutions, their territorial branches, expert institutions of municipal ownership, as well as forensic experts who are not employees of the mentioned institutions, and other specialists (experts) in the relevant fields of knowledge) to conduct relevant examinations (forensic examinations), which are carried out on the basis of special knowledge.It has been substantiated that the object of administrative and legal regulation of international cooperation of forensic examinations is forensic activity of forensic experts on their implementation of forensic examinations, including in the field of international cooperation, which is based on special knowledge and is aimed at obtaining a special opinion.It has been found out that the limits of forensic examination as an object of administrative and legal regulation of international cooperation are as follows: 1) the right of a forensic expert to conduct forensic examinations on the basis of national and international law; 2) provision of proper legal, organizational, financial and logistical support of forensic activities of its subjects (including the conduct of examinations of international importance); 3) ensuring international and legal (expert) cooperation during forensic examinations, etc.The importance of international and legal documents regulating the issues of international cooperation of forensic activity has been emphasized.
Keywords: forensic examination; special knowledge; an object; administrative and legal regulation; legislation; international cooperation; subjects